Peningkatan Kemampuan Perangkat Desa Dalam Pengelolaan Arsip Digital (E-Filing) Di Desa Aur Sati Kabupaten Kampar - Olivia, Monita; Malik, Alfian; Fatnanta, Ferry; Gussyafri, Haji; Novan, Andre; Ikhsan, Muhammad; Wibisono, Gunawan; Lubis, Shakila Fuadah; Maulidi, M Aldi; Fadhlurrahman, Fadhlurrahman (Journal of Community Engagement Research for Sustainability, 2024)
Aur Sati Village is one of the newly formed communities in Kampar Regency, Riau Province. Some administrative tasks, such as archive management, can improve village government services to the community. Village archives are currently stored manually and need to use digital archiving methods. Digital archive management can be used as a storage place for documents and can help overcome the lack of computer equipment owned by village officials. This program aims to increase the knowledge of village administrators regarding digital archive management (e-filing). The implementation of the e-filing program for Aur Sati Village officials is very useful in carrying out their administrative duties. There are three steps to the program: planning, implementation and success assessment. A survey with local leaders was part of the preparation step. An initial presentation, pre-test, and training on digital records management (e-filing) were conducted during the implementation phase using an app scanner, Google Drive, and Google Sheets. Village governments were given a post-test questionnaire to measure their skills during the evaluation phase. As a result, village governments showed a good understanding of e-filing and its management. Based on the post-test evaluation, most village officials and administrative staff in Aur Sati Village are able to digitally archive official letters (e-filing) and reduce the possibility of losing archives in the future.